Industrial Property Licensing Contracts are Exempted from Ban in Accordance with USA and European Law - Abdel Wahed, Raghad; Hussain, Akram (Journal of Legal Sciences, 2023)
Intellectual property rights of all kinds، and their nature، are considered a tool in the hands of their owner that enables him to monopolize the benefits that you confer on them without any dispute or mediation from anyone. Intellectual property on its intellectual product، and preventing others from exploiting it without obtaining the permission of its owner All of this is reflected positively on the progress of the industrial and commercial field، and this justifies the protection provided by the laws regulating intellectual property rights to its owner، whether at the national or international level، and with our recognition of the right of the owner of intellectual property rights to enjoy the exclusive use of his right، and the importance of providing legal protection for intellectual property rights Intellectual property، however، there are issues that are no less important than that، such as the abuse of intellectual property rights in a way that deviates from the normal use of its right، especially if the intention behind this use is to harm others، or that the interest that it aims to achieve is less than Damage caused by.